Worlds so strange and diverse : towards a genological taxonomy of non-mimetic literature. - Trebicki, Grzegorz (Cambridge Scholars Publis, 2015)
This book represents an analysis of contemporary fantasy (non-mimetic) literature in all its richness and diversity, and offers a preliminary definition of the major fields of taxonomical interest, in addition to marking some of the unmapped territories of ""fantastic"" fiction. In its first part, the book presents an overview of all major previous theoretical discussions of the issue, particularly those by Tzvetan Todorov, Rosemary Jackson, Darko Suvin, Brian Attebery, Marek Oziewicz and Farah Mendlesohn. The second part of the book provides an interesting comprehensive taxonomy of its own, b